Implementación del rediseño de la ingeniería para las operaciones de perforación en el bloque 54 de la cuenca de oriente del Ecuador (2016)
The following investigation presents the redesign of engineering for drilling operations in Block 54, located in the East Basin of Ecuador for subsequent field implementation and thus compare if there was a reduction in total drilling time respect to the 20D-2014 campaign, conducted in the same block. The redesign was based on bits, drilling fluids, solids control system, casing, cementing, directional drilling and hangers, based on past experience and operational problems occurred in the 2013-2014 campaign.